Food industrial biowaste-based magnetic activated carbons as sustainable adsorbents for anthropogenic mercury emissions. (15th June 2022) - Rodríguez-Sánchez, S.; Díaz, P.; Ruiz, B.; González, S.; Díaz-Somoano, M.; Fuente, E.
Abstract: Bio-derived magnetic activated carbons from industrial chestnut shell waste have been obtained through a novel, optimized and sustainable methodology where impregnation, pyrolysis, acid washing or other intermediate steps commonly used in the activation process were eliminated saving time, energy and costs. The resulting materials (MACs) were obtained at 220–800 °C showed interesting properties: textural (SBET up to 568 m 2 g-1) and magnetic (different iron species developed), depending on the activation temperature employed. Data showed outstanding results when MACs were tested for Hg removal in pollution emissions at 150 °C in lab-scale device. In MACs obtained at 500–600 °C, where the highest concentration of magnetite was found, the best Hg adsorption capacity was achieved, while it decreased when metallic iron or iron carbides were present (MACs obtained at 800 °C). Moreover, the difference of Hg0 removal/adsorption in N2+O2 and Simulated Flue Gas atmosphere between MACs obtained at 500 and 600 °C pointed out the influence on Hg removal of additional parameters, as surface chemistry and the existence of sulfur or chloride. The determination of Hg species in post-retention solids confirmed the mercury oxidation by high-valence iron ions (Fe3+) and the involvement of physisorption and chemisorption processes for the gas-solid interaction mechanism. Graphical abstract: Image 1 Highlights: Efficient and sustainable magnetic activated carbons (MACs) used for Hg removal. Anhydrous FeCl3 was employed as activating agent through a direct route. Magnetite played a critical role in MACs Hg adsorption against other iron species. The best Hg adsorption capacity was achieved in MACs obtained at 500–600 °C. Acid components in the flue gas may compete with Hg 0 for active sites.